NETRALITAS APARATUR SIPIL NEGARA DALAM PUSARAN POLITISASI BIROKRASI DI INDONESIA - Fitri Abidah Nur; Sri Budi Eko Wardani (Journal Publicuho, 2024)
This article aims to determine the link between ASN neutrality and the politicization of the bureaucracy in Indonesia, especially after direct regional head elections began in 2005. This change allowed serving regional heads to run for re-election, which could affect ASN neutrality and loyalty because regional heads have the authority to judge ASN performance and determining their structural positions. This research uses a qualitative approach. This research is also supported by library research, namely the study of written materials related to the research focus. The research results show that the politicization of bureaucracy that has occurred in Indonesia indicates that violations of ASN neutrality are still occurring. This can be seen from the use of state facilities, mobilization of ASN, compensation for job promotions, politicization of employee recruitment, promotion and depromotion of career positions.